Definition of the traditional African diet: a scoping review - Niu, Jizhao; Ockendon-Powell, Nina Frances; Alonge, Toluwanimi Ann; Papadaki, Angeliki (Frontiers in Nutrition, 2025)
BackgroundTraditional diets are increasingly studied for their purported health and environmental benefits. Promoting the traditional African diet (TrAfDi) could be a promising means of addressing the impacts of rapid dietary transitions in African countries. However, there is no consistent definition of this traditional dietary pattern. The aim of this scoping review was therefore to systematically explore, for the first time, the definition of the TrAfDi, as reported in the literature to date.MethodsSeven databases were searched, up to January 16th, 2023, for peer-reviewed studies and gray literature describing the TrAfDi. One reviewer screened articles, extracted data, and assessed article quality; an independent reviewer screened 10% of titles, abstracts, and full-text articles. Reporting followed the Preferred Reporting Items for Systematic reviews and Meta-Analyses for Scoping Reviews (PRISMA-ScR) guidelines.ResultsWe included 45 studies that defined a TrAfDi. The food groups characterizing the TrAfDi include cereals and their products, pulses, seeds and nuts and their products, and vegetables and their products. Other groups, cited less frequently, include fruits and their products, and roots, tubers, plantains, and their products. Maize was the most highly cited food item. Other, lesser-cited food items include cassava, cowpeas, fish, fruit, legumes, millet, and sorghum. Minor regional differences in the TrAfDi were observed when studies were segregated according to United Nations classifications. Differences were mainly observed between Western Africa and all other African regions, which, between them, do not appear to exhibit significant variation in the most frequently cited food groups. Few studies reported the quantities of foods consumed and the frequency of consumption.ConclusionThese findings provide important initial evidence on what may constitute a TrAfDi and indicate features of its regional characteristics, and are relevant to the development of public health policies seeking to tackle challenges of food insecurity, obesity, and non-communicable diseases in Africa. These will underpin future research to assess the TrAfDi's health and environmental impact, and to understand the cultural implications of shifting dietary patterns resulting from climatic, economic, and other factors. Future studies should also aim to strengthen regional representativeness and establish the quantities of foods that characterize this dietary pattern.Systematic review registrationhttps://osf.io/kvu2n.